2022
DOI: 10.1108/ijpsm-04-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

Servant leadership and organisational citizenship behaviour: the role of public service motivation and length of time spent with the leader

Abstract: PurposeThe study examined the influence of servant leadership on organisational citizenship behaviour (OCB) of employees in Ghana through the intervening roles of public service motivation (PSM) and the length of time spent with the leader.Design/methodology/approachA structured questionnaire was used to gather data from 328 randomly sampled respondents within the six metropoles in Ghana for data analysis. The partial least squares structural equation modelling (PLS-SEM) was used to address the hypotheses of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Furthermore, OCB can function as a mechanism that connects leadership behaviors and employee creativity, because OCB tends to be fostered through servant leadership, which leads to knowledge exchange among employees. Further evidence was documented in prior researches which showed that servant leadership positively affects OCB (Gnankob, Ansong, & Issau, 2022;Elche, Ruiz-Palomino, & Linuesa-Langreo, 2020;Tuan, 2017) and in turn, OCB leads to greater employee creativity (Xerri & Brunetto, 2013). According to the above arguments, the subsequent hypotheses are projected:…”
Section: Servant Leadershipmentioning
confidence: 81%
“…Furthermore, OCB can function as a mechanism that connects leadership behaviors and employee creativity, because OCB tends to be fostered through servant leadership, which leads to knowledge exchange among employees. Further evidence was documented in prior researches which showed that servant leadership positively affects OCB (Gnankob, Ansong, & Issau, 2022;Elche, Ruiz-Palomino, & Linuesa-Langreo, 2020;Tuan, 2017) and in turn, OCB leads to greater employee creativity (Xerri & Brunetto, 2013). According to the above arguments, the subsequent hypotheses are projected:…”
Section: Servant Leadershipmentioning
confidence: 81%
“…The distinction between servant leadership and PSM is also reinforced in some recent scholarship in public sector context. For example, a few recent studies have examined PSM as an intervening variable that facilitates servant leadership to manifest as employee outcomes (Bayram & Zoubi, 2020;Gnankob et al, 2022;Nguyen et al, 2022;Schwarz et al, 2016;Shim & Park, 2019;Tuan, 2016).…”
Section: Genesis Of Servant Leadershipmentioning
confidence: 99%
“…Servant leadership has been identified as an antecedent of PSM in multiple countries such as China (Liu et al, 2015(Liu et al, , 2018, Ghana (Gnankob et al, 2022), Korea (Shim and Park, 2019) and Vietnam (Tuan, 2016). Although no studies specific to servant leadership in Indian public sector has been published to the best of our knowledge, studies conducted on mixed sample consisting of both public and private sector organizations suggest high mean levels of servant leadership in India and demonstrate a positive role of servant leadership in reducing employee turnover (Kashyap and Rangnekar, 2016).…”
Section: Psm and Leadershipmentioning
confidence: 99%
“…display higher PSM for public service providers. Studies indicate a positive relationship between servant leadership and PSM in multiple countries (see Liu et al, 2015;Tuan, 2019;Gnankob et al, 2022). Servant leadership has been found to improve PSM at both group and individual levels (Shim and Park, 2019) and PSM has been found to mediate the effect of servant leadership on OCB (Gnankob et al, 2022) and knowledge sharing (Tuan, 2016).…”
Section: Formulation Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation